An improvement in performance of mobile ad hoc networks using modified route maintenance. (November 2016) - Sharma, Dhirendra Kumar; Patra, Amar Nath; Kumar, Chiranjeev
Abstract: A mobile ad hoc network (MANET) is a temporary network where nodes are free to move in a given area. Due to this dynamic nature, links in the routes break. Often backup routing is used as a solution in which alternate route tables are used to continue the data transfer. In this paper, we discuss the shortcomings of the existing backup routing, which is due to their inadequate ways of updating alternate route table information by route maintenance. In several routing protocols, hello messages are periodically broadcasted to update the neighbour table entries which help in detecting link failure. We propose an efficient route maintenance mechanism in AODV routing protocol employing the benefits offered by hello messages. Simulation results show that our proposed modified route maintenance (MRM) scheme significantly improves the performance of MANET.